Brusberg Berichte 23. - Galerie Brusberg, Hannover (Hannover : Galerie Brusberg, 1977)
Böckman, Bengt ; Calder, Alexander ; Hausner, Rudolf ; Jäger, Bernhard ; Leissler, Arnold ; Patrick, Wolfgang ; Paul, Peter ; Oppermann, Wolfgang ; Ryohei, Tanaka ; Sawai, Noboru ; Sugai, Kumi ; Schwarz, Reiner ; Szymanski, Rolf ; Voss, Jan ; Wunderlich, Paul
boek